2005
DOI: 10.1155/ijmms.2005.1171
|View full text |Cite
|
Sign up to set email alerts
|

On the generalized Roper‐Suffridge extension operator in Banach spaces

Abstract: The generalized Roper-Suffridge extension operator in Banach spaces is introduced. We prove that this operator preserves the starlikeness on some domains in Banach spaces and does not preserve convexity in some cases. Furthermore, the growth theorem and covering theorem of the corresponding mappings are given. Some results of Roper and Suffridge and Graham et al. in C n are extended to Banach spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They generalized this extension operator in C n and discussed their properties (see [3][4][5][6][7][8][9][10][11], etc.). Recently, we generalized the Roper-Suffridge operator to Banach spaces in [14,23]. We have proved that the generalized Roper-Suffridge extension operator preserves the biholomorphic ε starlikeness on some domains in Banach spaces for ε ∈ [0, 1].…”
Section: From (42) and (43) We Havementioning
confidence: 99%
“…They generalized this extension operator in C n and discussed their properties (see [3][4][5][6][7][8][9][10][11], etc.). Recently, we generalized the Roper-Suffridge operator to Banach spaces in [14,23]. We have proved that the generalized Roper-Suffridge extension operator preserves the biholomorphic ε starlikeness on some domains in Banach spaces for ε ∈ [0, 1].…”
Section: From (42) and (43) We Havementioning
confidence: 99%
“…Recently, we generalized Roper-Suffridge operator to Banach spaces in [13,21]. Now we introduce a linear operator in purpose to construct some other concrete examples about the biholomorphic convex mappings on B in a Hilbert space X.…”
Section: Remarkmentioning
confidence: 99%
“…In fact several types of generalizations have been considered (see refs. [10,12,15,[18][19][20][36][37][38]). …”
Section: Generalizations Of the Roper-suffridge Extension Operatormentioning
confidence: 99%
“…M. S. Liu and Y. Zhu [18,20] gave a generalization to complex Banach spaces. In particular, they considered operators and domains analogous to (4.2) and (4.3), and showed that ε-starlikeness is preserved.…”
Section: Modifications Of the Coefficient Ofzmentioning
confidence: 99%